(untitled) (Bangladesh Journal of Urology, 2020)
Background: Nephrectomy is indicated in patients with an irreversibly damaged kidney. The nephrectomy can be performed through open or laparoscopic procedure. Although there is evidence that laparoscopy is the preferred choice, additional evidence is indicated. Objective: To compare the outcomes of nephrectomy through open and laparoscopic procedures. Methods: This prospective observational study was conducted in the Department of Urology, National Institute of Kidney Diseases and Urology, Sher-e-Bangla Nagar, Dhaka from July 2017 to December 2019 over a period of two and half years. In this study, 13 patients had laparoscopic nephrectomy and 17 patients had open nephrectomy. Operative time, length of hospital stay, loss of bleeding, transfusion requirement, peri and post-operative complications were recorded and compared. SPSS 12 was used for analysis. Categorical data were compared with Chi-square test and numerical data were compared with unpaired t test. Results: Maximum patients were more than 40 year old and mean age was 43.53 ± 5.55 years & 41.46 ± 6.31 years in open & laparoscopic nephrectomy group respectively. Male and female ratio was almost similar in both groups. Operative time for open nephrectomy was significantly lower than operative time for laparoscopic nephrectomy (147.9 ± 34.2 vs 184.6 ± 33.3 min; p=0.004). Mean length of post-operative hospital stay was significantly longer for patients receiving open surgery than for patients receiving laparoscopy (7.06 ± 3.67 days vs 3.92 ± 0.86 days; p = <0.001). There was no significant difference in mean postoperative time to oral intake for patients receiving open and laparoscopic nephrectomy (24.71 ± 2.91 hours and 24.00 ± 0.00 hours; p = 0.391). Per-operative complications occurred in 9 (52.9%) patients in the open nephrectomy group and in 3 (23.1%) patients in laparoscopic nephrectomy group. There was no significant group difference in complication rates (P = 0.098). Pain was reduced significantly in both groups. In each follow up, VAS was significantly lower in laparoscopic nephrectomy group than open nephrectomy group groups. Conclusion: The overall outcomes of the two procedures were similar. Pain was significantly less in laparoscopic nephrectomy. Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.52-55